Advancing Gender Equality in Healthcare Leadership: Protocol to Co-Design and Evaluate a Leadership and Mentoring Intervention in Tanzania - Doreen Mucheru; Henry Mollel; Brynne Gilmore; Anosisye Kesale; Eilish McAuliffe (Ubiquity Press, 2024)
Background: Women constitute almost two thirds of the health and social workforce. Yet, the proportion of women in decision-making positions remains significantly low leading to gender inequities in access to and appropriateness of healthcare. Several barriers which limit women's advancement to leadership positions have been documented and they generally constitute of gender stereotypes, discrimination and inhibiting systems; these hinderances are compounded by intersection with other social identities. Amelioration of the barriers has the potential to enhance women's participation in leadership and strengthen the existing health systems. Objective: This protocol describes a proposed study aimed at addressing the organisational and individual barriers to the advancement of women to leadership positions in the Tanzanian health sector, and to evaluate the influence on leadership competencies and career advancement actions of the female health workforce. Method: The study utilises a gender transformative approach, co-design and implementation science in the development and integration of a leadership and mentorship intervention for women in the Tanzanian health context. The key steps in this research include quantifying the gender ratio in healthcare leadership; identifying the individual and organisational barriers to women's leadership; reviewing existing leadership, mentorship and career advancement interventions for women; recruiting programme participants for a leadership and mentorship programme; running a co-design workshop with programme participants and stakeholders; implementing a leadership and mentorship programme; and conducting a collaborative evaluation and lessons learnt. Conclusions: This research underscores the notion that progression towards gender equality in healthcare leadership is attained by fashioning a system that supports the advancement of women. We also argue that one of the pivotal indicators of progress towards the gender equality sustainable development goal is the number of women in senior and middle management positions, which we hope to further through this research.